2021
DOI: 10.1039/d1ra03820f
|View full text |Cite
|
Sign up to set email alerts
|

CDK4/6 inhibitors: a brief overview and prospective research directions

Abstract: The discovery of cyclin-dependent kinases (CDK) and their mechanism in regulating the cell cycle process was considered a game-changer in cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 69 publications
0
26
0
Order By: Relevance
“…Compound 66 , on the other hand, promoted apoptosis primarily through the intrinsic route, with direct inhibition of CDK6. 44 Shi et al proposed a new class of CDK4/6 inhibitors: imidazo[1′,2′:1,6]pyrido(2,3- d )pyrimidine analogs. 44,45 In the Colo-205 as well as U87MG cell lines, CDK4/6 was found to be effectively suppressed by compounds 70 and 71 .…”
Section: Molecular Targets Of Pyrido[23-d]pyrimidine Derivativesmentioning
confidence: 99%
“…Compound 66 , on the other hand, promoted apoptosis primarily through the intrinsic route, with direct inhibition of CDK6. 44 Shi et al proposed a new class of CDK4/6 inhibitors: imidazo[1′,2′:1,6]pyrido(2,3- d )pyrimidine analogs. 44,45 In the Colo-205 as well as U87MG cell lines, CDK4/6 was found to be effectively suppressed by compounds 70 and 71 .…”
Section: Molecular Targets Of Pyrido[23-d]pyrimidine Derivativesmentioning
confidence: 99%
“…The experimental results indicated that hUC-MSC-CM can effectively reduce the production of intracellular ROS and promote the recovery of cell motility. Cell cycle arrest can lead to a decrease in the ability of cells to proliferate [59]. UVB irradiation blocked the transition from the G1 phase to the G2 phase of the cell cycle in HaCaT cells, resulting in decreased cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin-dependent kinase 4 (CDK4) is an oncogene that is particularly important for controlling the cell cycle and has been demonstrated in many types of cancer [ 86 , 87 ]. CDK4 and CDK6 inhibitors are used in treating patients with hormone receptor–positive breast cancers [ 88 , 89 ]. Therefore, it is clinically warranted to influence the higher level of expression controlling these proteins, i.e., the use of the hsa_circ_0014235 inhibitor.…”
Section: Exosomes As Chemoresistance Mediatorsmentioning
confidence: 99%